The walking dead. Vol. 21, All out war, part two - Kirkman, Robert; Kirkman, Robert (Walking dead, 2014)
An epidemic of apocalyptic proportions has swept the globe, causing the dead to rise and feed on the living. In a matter of months society has crumbled, no government, no grocery stores, no mail delivery, no cable TV. In a world ruled by the dead, we are forced to finally start living.